The Urgency of Job Loss Security Program for the Protection of Human Rights - Lasatu, Asri; Surahman , Surahman; Awaluddin , Awaluddin; Lubis, Putri Mei; Jubair, Jubair (Universitas Lampung, 2024)
Jaminan Kehilangan Pekerjaan (JKP) or The Job Loss Security Program is a recent government initiative designed to enhance legal, economic, and social protection for workers affected by Termination of Employment. This program needs proper supervision for optimal contribution to the community well-being. This normative legal research used both statutory and conceptual methods to answer the central research question regarding the urgency of the JKP program in safeguarding human rights. The findings indicate that the JKP program significantly aids workers by providing financial support, facilitating access to labor market information, and enhancing skills through job training, thereby helping them meet their own and their families' needs.